2016
DOI: 10.1002/hed.24641
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA detection in fine‐needle aspirates as indicator of human papillomavirus–positive oropharyngeal squamous cell carcinoma: A prospective study

Abstract: HPV16 DNA detection in fine-needle aspirations from neck masses is reliable and HPV16 DNA in a metastasis is a strong indicator of an HPV-positive oropharyngeal SCC. © 2016 Wiley Periodicals, Inc. Head Neck 39: 419-426, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…When the only clinical manifestation is represented by cervical lymphadenopathy, direct HPV testing on lymph nodes is recommended in order to help identify the tumour primary site . In fact, it has been shown that HPV‐positivity in metastatic lymph nodes represents a strong predictor of primary tumour localisation in the oropharynx . To obtain diagnostic material from pathological lymph nodes, fine‐needle aspiration (FNA), which represents a simple and non‐invasive procedure, is preferred to open surgical biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…When the only clinical manifestation is represented by cervical lymphadenopathy, direct HPV testing on lymph nodes is recommended in order to help identify the tumour primary site . In fact, it has been shown that HPV‐positivity in metastatic lymph nodes represents a strong predictor of primary tumour localisation in the oropharynx . To obtain diagnostic material from pathological lymph nodes, fine‐needle aspiration (FNA), which represents a simple and non‐invasive procedure, is preferred to open surgical biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…The biopsy technique should be established and performed by fine needle aspiration (FNA), or possibly by an open biopsy if the histological diagnosis is unclear or more tissue is required in cases of malignant lymphoma. Fine needle aspiration biopsy allows the pathologist to see the cells aspirated from the lesion and therefore requires experience.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirated cells can be evaluated by flow cytometry or with immunologic markers (e.g., human papillomavirus detection). In every case, FNA is a test and should be interpreted in the context of the whole clinical circumstances …”
Section: Discussionmentioning
confidence: 99%
“…Needle biopsy is used to obtain samples for cytology, 271,272 for microbial stains and culture, 273,274 for genomic probes from localized sites of infection, [275][276][277] or for flow cytometry of viral antigens. 278 Each type of sample has particular requirements related to representative cells and handling, and each is fraught with inadequacy related to sample representativeness.…”
Section: Infectious Diseasementioning
confidence: 99%